Study Of Turbulence Characteristics Of An Oscillatory Flow Conditions In Thermoacoustic Using Experimentally Validated Two-Equations Turbulence Model - Mohd Sa’at, Fatimah Al-Zahrah; Mat Tokit, Ernie; Mohd Ghazali, Normah; Putra, Azma (UTeM, 2019)
Oscillatory flow condition is a fluid flow condition that is less understood especially with the presence of structure as found in thermoacoustic environment. Thermoacoustics is a principle of science that involves conversion between thermal and acoustic energy to produce either power or cooling effect. Fundamental studies related to turbulence in oscillatory flow conditions of thermoacoustic environment is needed to help understand potential losses or gain in the system due to the presence of turbulence. This is done through this project where methods such as experiments and computational modellings are used. The test rig was designed using a design software known as DeltaEC. Upon successful design, the rig is fabricated and installed in Turbomachinery Lab, FKM. CFD models of oscillatory flows inside thermoacoustic environment were also solved using ANSYS Fluent and the results are then validated with the experimental works and verified with theoretical equations. Comprehensive analysis leads to the definition of several vortex shedding patterns, boundary layer thickness behavior and relatively new definition of entrance region in oscillatory flow condition was also discovered. The resulting velocity amplitude of flow are then used to calculate the Reynolds number and then the results are mapped into the previously defined turbulence region for oscillatory flow condition in pipe. Results showed that the presence of structure leads to early start of turbulence depending on the length of structure and frequency of the flow. Two graduated MSc students were trained, eight (8) SCOPUS/ISI journal papers were published, 3 articles were submitted into conference proceedings, 1 short publication is also published via participation in MERDs 2017. The research works were presented at three (3) local conferences/symposium and one (1) international conference oversea. One (1) “best paper presentation” award was received at the international conference. Apart from the development of skills and instrumentation for the research group laboratory, the project has contributed towards fundamental understanding of fluid dynamics of the complex oscillatory flow conditions which will help better design for future thermoacoustic energy system as well as other oscillatory flow conditions in another fields such as blood flow and ocean wave.